(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Exploitation and suffering of the Dalit and subaltern class has been one of the major themes of literature. The novels of Dr. Mulk Raj Anand depict a realistic and sympathetic portrait of the Dalit and subaltern class of his time in India focusing on how they suffer in their struggle of managing their livelihood and how they are exploited by the upper class and well to do people in the society depriving them of their every prospect of opportunity. For his presentation the humanist has picturised the lives of the sweepers, peasants, the daily wagers, the workers, and the soldiers, all other depressed and oppressed people of his notice. The focus on the prevailing pains and plights of the have-nots is like revolutionary in his part. We find a true Indian society in his novels with special attention to the misery of the poor.This research paper is an attempt to study how during 1930’s, in India the Dalits and the subaltern class were neglected and exploited. They did not enjoy the minimum human dignity and had to go through a constant struggle for their survival. Gandhi, as a social reformer, redeemed the life of these untouchables and underdogs of society by standing like a rock. He was not only a social reformer but also brought religious renaissance among the Hindus.